Some Sufficient Conditions for Starlikeness and Convexity of Order - Yi-Ling Cang; Jin-Lin Liu (Journal of Applied Mathematics)
We derive certain sufficient conditions for starlikeness and convexity of order of analytic functions in the unit disk. Applications are indicated for the subordination results to electromagnetic cloaking.